CFD-DEM study on the mixing characteristics of binary particle systems in a fluidized bed of refuse-derived fuel. (2nd January 2019) - Wang, Li-Jun; Wei, Guang-Chao; Duan, Shu-Ping; Hou, Qin-Fu
ABSTRACT: The fluidization of quartz in the fluidized bed has great influence on the combustion and gasification of refuse-derived fuel (RDF). The combined computational fluid dynamics (CFD) and discrete element method (DEM) approach was used to explore the gas-solid hydrodynamics and mixing characteristics in a three-dimensional fluidized bed. All numerical analyses were performed referring to the experiments (Goldschmidt, Beetstra, and Kuipers2004 ). The simulation results indicated that the quartz volume fraction agrees well with the experimental data. Furthermore, the cylinder-shaped RDF particles can mix well with the quartz particles as they were added from upside. For binary systems, it is necessary to investigate solid flow characteristics as well as pressure drops and examine the influence of superficial gas velocity on the solid mixing. Two main parameters are discussed: mixing degree and the time required to reach the steady state. It is also found that inlet gas velocity and particle properties (particle density ratio, shape and size) are significant factors on particle mixing in a fluidized bed.